Management, morphological and genetic diversity of domesticated agaves in Michoacán, México - Gonzalo D. Álvarez-Ríos; Fernando Pacheco-Torres; Carmen Julia Figueredo-Urbina; Alejandro Casas (BMC, 2020)
Abstract Background Pulque is a fermented beverage prepared with sap of Agave species in Mexico. Management of agaves for this purpose has motivated domestication of some species and high phenotypic variation that commonly causes uncertainty about the taxonomic identity of varieties traditionally managed by people. This study assumed that varieties of crop species continually arise from mutations, sexual reproduction and hybridization, among other processes, and some of them are favoured and maintained by humans. Identifying these varieties may be difficult and a challenging issue for botanists and evolutionary biologists studying processes of domestication. Through a case study, we analysed the traditional varieties of agaves used to produce pulque in Michoacán, Mexico. We aimed at identifying the varieties, analysing the relatedness among them and developing a methodological approach that could help solve taxonomic problems and study variation under domestication of this and other plant groups. We documented (1) the traditional varieties of agave used and their identity, (2) how these varieties are perceived, used and managed by the local people and (3) how management influences phenotypic and genetic variation among varieties. Methods We interviewed pulque producers in two localities of the state of Michoacán, Mexico, where we recorded management practices of agaves, the traditional varieties used, the attributes characterizing those varieties, the varieties preferred by people, and features and mechanisms of selection. We conducted multivariate analyses of morphological features of the agave varieties, as well as genetic diversity and genetic distance studies among agave varieties through 11 nuclear microsatellites. Results Seven traditional varieties of Agave were recorded in the study area. Multivariate analyses of morphology identified varieties belonging to the species A. salmiana, A. mapisaga and, presumably, A. americana. The preferred varieties have morphological features selected to make easier their management and produce higher sap yields. Genetic diversities (H E = 0. 470 to 0.594) were high compared with other Agave species with similar life history traits and use. Genetic distance analyses grouped the varieties "Verde" and "Negro" (identified as A. salmiana), whereas the varieties "Tarímbaro" and "Listoncillo" (identified as A. mapisaga) formed another group. The varieties "Blanco" and "Carrizaleño" (most probably being A. americana) clustered with varieties of A. salmiana, whereas the variety "Cenizo" appeared as a distinct group. Bayesian analysis indicated that most individuals of varieties of A. salmiana form a group and those of the varieties of A. mapisaga form another, whereas individuals of the varieties putatively belonging to A. americana clustered in similar proportions with both groups. Conclusions The traditional pulque production in the study area is an ongoing practice. It is still an important source of products for direct consumption by households and generation of economic incomes and as part of the cultural identity of local people. The most used traditional variety exhibited a marked gigantism, and although these agaves are mainly asexually propagated, populations have high genetic diversity. The local producers promote the maintenance of different traditional varieties. Our study shows the value of an integral research approach including ethnobiological, morphological and genetic information to clarify the state of variation influenced by humans on agaves, but it would be helpful to study other organisms under domestication. In addition, such approach would help to document human and non-human mechanisms generating crop varieties managed by local people.